Program Kampus Mengajar Angkatan 2 Tahun 2021 Meningkatkan 5 Aspek Literasi Peserta Didik - Hikmawati Hikmawati Hikmawati; Talita Gita Andani; Faradilla Ngesti Habibah; Maziya Malkan; Firda Aprilia Insani (Kappa Journal, 2022)
Basic literacy is one of the competencies that must be possessed by 21st century students. The basic literacy of students is still relatively low, so the government makes various efforts to improve literacy, one of which is through the Independent Learning-Independent Campus (MBKM) policy, namely the Teaching Campus. The purpose of this study was to improve 5 aspects of student literacy at SMP Negeri 19 Mataram through the Teaching Campus Program Batch 2 in 2021. The aspects studied consisted of literacy, numerization, science, digital, and culture and citizenship. Each aspect of literacy has certain indicators. The research was carried out from August to December 2021 with a total of 20 students. The assessment of each indicator for each aspect of literacy uses a scale of 4, and is converted in percentage form with ratings of Less (K), Enough (C), Good (B), and Very Good (A). The increase in literacy scores was calculated using N-gain with three criteria, namely Low, Medium, and High. The results showed that the lowest literacy aspect was digital literacy while the highest literacy was scientific literacy. The average literacy value during the initial assessment was 51.6 with a rating of Less (K), while at the final assessment it was 82.0 with a rating of Good (B). The N-gain value was obtained at 63.1 which was in the Medium criteria. Thus, it can be concluded that the Teaching Campus Program Batch 2 in 2021 has improved 5 aspects of student literacy at SMP Negeri 19 Mataram.